2017
DOI: 10.1007/s12046-017-0662-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis, design and implementation of sensorless V/f control in a surface-mounted PMSM without damper winding

Abstract: This paper presents a novel, reliable and efficient V/f control implementation on a 8-pole, 750 rpm, 5 kW surface-mounted permanent magnet synchronous motor (PMSM) without damper winding. In the absence of a damper winding, open loop V/f control of SM is inherently unstable, particularly at high speeds. Stabilisation can be done with proper stator frequency modulation in accordance with the change in rotor speed to provide for effect of damping. This has been implemented here without use of any shaft-mounted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, open loop variable frequency drive-based voltage source control may not be stable for all frequencies and it may be necessary to include a stabilizing inner loop. The stability and inner loop feedback stabilization of a PMSM with an outer open loop variable frequency drive and a constant load have been considered by many authors [25][26][27][28][29] and will not be reconsidered here. Yet, the methodology is particularly suitable for HTS PMSMs, as the stator resistance of these machines is particularly low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, open loop variable frequency drive-based voltage source control may not be stable for all frequencies and it may be necessary to include a stabilizing inner loop. The stability and inner loop feedback stabilization of a PMSM with an outer open loop variable frequency drive and a constant load have been considered by many authors [25][26][27][28][29] and will not be reconsidered here. Yet, the methodology is particularly suitable for HTS PMSMs, as the stator resistance of these machines is particularly low.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a generic voltage source controller based on a multi-loop control structure and an inner stabilization loop are being developed to control a typical HTS PMSM with a dynamic propeller load that is not constant, and the results of that study will be reported independently. The dynamic model is altered to include the load angle dynamics and the inner loop control law is synthesized by the method reported in [29]. Scaling laws for matching the results of this study to other HTS PMSMs are used to facilitate the design of a distributed propulsion system for an all-electric aircraft.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is a common phenomenon that the rotor displacement can vary in real time, which requires a more difficult installation accuracy for the position sensor and a higher cost and reducer reliability. Therefore, the sensorless control strategy has become a leading issue in the PMSM control field [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%